PENGARUH OPINI AUDIT, REPUTASI AUDITOR DAN AUDIT DELAY TERHADAP MINAT INVESTASI - Agam Yulianto; Yefta Andi Kos Noegroho (Universitas Muhammadiyah Jember, 2020)
This study aims to look at the effect of Audit Opinion, Auditor Reputation and Audit Delay on investment interests, especially among students. This study will use primary data obtained through a questionnaire distributed directly to respondents during face-to-face capital market school courses and also through Google forms distributed via email to respondents who did not attend capital market school courses in the even semester of the 2019 school year / 2020 as a research instrument. Data collected through the questionnaire will then be processed using quantitative methods. The population in this study are active students who have already or are investing. Of the total population that matches the predetermined criteria, 100 data will be taken as samples to be processed. The collected data will be analyzed using the multiple linear regression method with the help of the Statistical Package for the Social Sciences application. Before the data was processed, the validity and reliability of the questionnaire was tested and also the classic assumption test to see the effect of the three independent variables on investment interest as the dependent variable used in this study. The results of this study indicate that the Auditor's Reputation does not influence the students' interest to invest. While the Audit Opinion and Audit Delay examined in this study have an influence on student investment interests.